Ochnaflavone, a Naturally Occuring Biflavonoid: Pharmacology and Prospects for Future Research - Monica Mbaraka Ndoile (Archives of Current Research International, 2018)
Aims: To profile and address matters surrounding ochnaflavone (1), derivatives and analogues. Methodology: Papers concerning ochnaflavone, derivatives and analogues were accessed from search engines such as google scholar and pubmed. Results: Ochnaflavone and derivatives are compounds bearing ether linkage between the two B-rings of the two flavonoid moieties. These compounds are known to possess potent biological activities such as anti-inflammatory, anticancer, anti HIV and antimicrobial. Conclusion: In this paper, an overview summary of ochnaflavone, derivatives and analogues from past to present is presented. Thus, the paper provides a sense of focus to researchers; seal breaks the unattended matters, and therefore, spearheads new research areas concerning these compounds.